2012
DOI: 10.1590/s0102-695x2011005000204
|View full text |Cite
|
Sign up to set email alerts
|

Quality control and TLC profile data on selected plant species commonly found in the Brazilian market

Abstract: Abstract:The use of thin-layer chromatography (TLC) is a commonplace practice and can be of signifi cant help to different laboratories with quality control, especially those that work with plant extracts and phytotherapeutics. This study evaluated ten species of plants (Schinus terebinthifolius, Arctium lappa, Trichilia catigua, Camellia sinensis, Mikania glomerata, Croton moritibensis, Achyrocline satureioides, Heteropterys aphrodisiaca, Plantago major, Arctostaphylos uva-ursi) that are commonly sold by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
0
19
0
7
Order By: Relevance
“…It is notable for its simplicity, low cost and speed, and it is worth noting the ease in which it can qualitatively detect the presence of compounds with the aid of reference standards 40 . To enable a more efficient separation process, the technological advances in the area of chromatography have led to the development of equipment that performs the application in a partially or totally automated way, ensuring volume reproducibility and homogeneity in this application 41,42 . The TLC analysis of samples revealed that stem bark and pods from L. ferrea presented a band with same coloration and displacement as that observed for the standard solution of gallic acid.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable for its simplicity, low cost and speed, and it is worth noting the ease in which it can qualitatively detect the presence of compounds with the aid of reference standards 40 . To enable a more efficient separation process, the technological advances in the area of chromatography have led to the development of equipment that performs the application in a partially or totally automated way, ensuring volume reproducibility and homogeneity in this application 41,42 . The TLC analysis of samples revealed that stem bark and pods from L. ferrea presented a band with same coloration and displacement as that observed for the standard solution of gallic acid.…”
Section: Discussionmentioning
confidence: 99%
“…8 The TLC is also very useful for preliminary study before other instrumental techniques are applied. 9,10 The use of TLC for separation and purification of plant constituents depends on their size, shape and charge.…”
Section: Introductionmentioning
confidence: 99%
“…Application of HPTLC fingerprints in determination of quality of botanicals was explained by Nicoletti 40 . Braz et al 41 have used HPTLC technique to establish quality standards of selected plant species commonly found in the Brazilian market. HPLC is a popular method for the analysis of herbal medicines because of its easiness and HPLC analysis is not limited by the volatility or stability of the sample compound.…”
Section: Resultsmentioning
confidence: 99%